Vulnerabilities in the semiconductor supply chain - Haramboure, Antton (OECD Publishing, 2023)
Semiconductors are a critical input into a wide range of downstream industries, including the wider information communications technology industry, electronics and motor vehicles. Semiconductor shortages can have large adverse effects on output in these industries, with ripple effects on the broader economy, as highlighted by recent supply chain disruptions. This paper maps cross-country and cross-sectoral dependencies in the semiconductor value chain based on new OECD Inter-Country Input-Output data that allow to analyse the semiconductor industry separately from the wider computer and electronics value chain. It further discusses policy options to reduce the economic consequences of shocks to the semiconductor value chain while preserving the benefits of global sourcing
Keywords: Science and Technology; Trade